Rural Nonfarm Employment andIncomes in the Himalayas - Maja Micevska; Dil Bahadur Rahut (Indian Council for Research on International Economic Relations (ICRIER), 2008)
Nonfarm activities generate on average about 60 percent of rural households' incomes in the Himalayas. This paper analyzes the determinants of participation in nonfarm activities and of nonfarm incomes across rural households. A unique data set collected in the Himalayan region of India allows us to deal with the heterogeneity of rural nonfarm activities by using aggregations into categories that are useful both analytically and for policy purposes. We conduct an empirical inquiry that reveals that education plays a major role in accessing more remunerative nonfarm employment. Other household assets and characteristics such as land, social status, and geographical location also play a role
Keywords: O15; O18; Q12; R11; 330; Nonfarm employment; Rural households; Incomes; Education; India; Soziale Lage; Privater Haushalt; Haushaltseinkommen; Ländlicher Raum; Himalaya; Asien